KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DILIHAT DARI FAKTOR INTERNAL DAN EKSTERNAL (Studi Kasus pada Wajib Pajak Desa Bugel Kec. Godong Kab.Grobogan) - Aulia Indira Lailyatussoqiba; YULI CHOMSATU; SUHENDRO SUHENDRO (JURNAL WIDYA GANECWARA, 2019)
The purpose of this study is to determine the internal factors ( knowledge and awareness of the taxpayer ) as well as external factors that affect the tax penalty tax compliance in paying land and buildings tax at Bugel Village . The object of this research is Bugel Village, which according to data at the Grobogan Central Bureau of Statistics in 2017 figures shows the difference between nominal payment realization and nominal target.  The technique of collecting sample in this study used simple random sampling with a total sample of 92 taxpayers , the sample calculation refers to the Slovin formula . Based on the results of multiple regression analysis assisted with SPSS, showed that knowledge of the tax does not affect the level of tax compliance in paying Land and Buildings tax in Bugel Village, while awareness of taxpayers and tax sanctions affect on taxpayer compliance in paying Land and building taxes in Bugel Village .